\(A=x-2\sqrt{x}=x-2\sqrt{x}+1-1=\left(\sqrt{x}-1\right)^2-1\)
Vì \(\left(\sqrt{x}-1\right)^2\ge0\) với mọi x>=0
=> \(\left(\sqrt{x}-1\right)^2-1\ge-1\)
Vậy GTNN của A là -1 khi x=1
\(A=x-2\sqrt{x}\)
\(=x-2\sqrt{x}+1-1\)
\(=\left[\left(\sqrt{x}\right)^2-2.1.\sqrt{x}+1^2\right]-1\)
\(=\left(\sqrt{x}-1\right)^2-1\)
Ta có : \(\left(\sqrt{x}-1\right)^2\ge0\)
\(\Rightarrow\left(\sqrt{x}-1\right)^2-1\ge-1\)
Dấu " = " xảy ra khi và chỉ khi \(\sqrt{x}-1=0\)
\(\Leftrightarrow\sqrt{x}=1\)
\(\Leftrightarrow x=1\)
Vậy \(Min_A=-1\) khi và chỉ khi \(x=1\)